Pengaruh Permainan Maze Angka Terhadap Kemampuan Berhitung Anak Usia Dini : Studi Pre-Eksperimen di TK Al-Iman Desa Paringgonan - Silfa Hafizah Pulungan; Ertisartika Mayunni Pulungan; Rahyana Hasibuan (Information Technology and Science (ITScience), 2026)
The development of children's numeracy skills in early childhood is a crucial aspect in supporting their readiness to enter the next level of education. This study aims to determine whether there is an effect of number maze games on early childhood counting skills at Al-Iman Kindergarten in Paringgonan village. Using quantitative research methods with an experimental approach. The design uses one-group pretest-posttest, this study involved 28 children as samples. The instruments used were observation and documentation. Data were analyzed using descriptive statistics, complemented by prerequisite tests in the form of normality and homogeneity tests. Hypothesis testing was done with paired sample t-test. The results of the study based on hypothesis testing obtained a tcount of 10,31 while the ttable price was obtained at 2,05. If the acquisition of the tcount value is compared with the ttable value, it is known that the tcount is greater than the ttable, namely 10,31> 2,05. Based on these results, of course, it can be concluded that the hypothesis that has been proposed is accepted, namely that there is an influence between the number maze game on the counting ability of early childhood in Al-Iman Kindergarten, Paringgonan Village.